A Post-Keynesian macroeconomic policy mix as an alternative to the New Consensus approach - Eckhard Hein; Engelbert Stockhammer (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2007)
In a Post-Keynesian (PK) model we show that inflation targeting monetary policies, as the main stabilisation tool proposed by the New Consensus Model (NCM), in the short run are only adequate for certain values of the model parameters, but are either unnecessary, counterproductive, or limited in their effectiveness for other values. Taking into account medium-run cost and distribution effects of interest rate variations renders monetary policies completely inappropriate as an economic stabiliser. Based on these results we argue that the NCM macroeconomic policy assignment should be replaced by a PK assignment. Enhancing employment without increasing inflation will be possible if macroeconomic policies are coordinated along the following lines: The central bank targets distribution between rentiers, on the hand, and firms and employees, on the other hand, and sets low real interest rates, wage bargaining parties target inflation and fiscal policies are applied for short- and medium-run real stabilisation purposes.
urn:nbn:de:101:1-2008081894
Keywords: E12; E50; 330; Macroeconomic policies; New Consensus Model; Post-Keynesian Model; inflation targeting